2022
DOI: 10.1108/jpbm-08-2021-3606
|View full text |Cite
|
Sign up to set email alerts
|

What draws voters to brandidates and why? – Political orientation, personal satisfaction, and societal values on presidential candidates’ brand personality

Abstract: Purpose The purpose of this study is to determine the impact of voters’ personal and societal values on presidential candidate brand personality preference. In addition, the research examines which brand personalities are deemed most and least important. This research meets the growing demand to further understand how voters develop preferences for brandidates. Design/methodology/approach Voters ranked which presidential brand personalities they deemed most important in a candidate as well as which of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 119 publications
0
0
0
Order By: Relevance
“…This is in the form of the view that this content features Youtubers who live a fun lifestyle, which is filled with several entertaining activities. More satisfied individuals tend to have a preference for certain personality attributes in someone they admire, which can be influenced by progress in that individual (Harrison et al, 2023). It can be concluded that the results of this study are in line with previous research conducted by Malik et al, (Malik et al, 2023) which states that Fun has a very good impact on improvement Overal Perceived Image owned by YouTubers.…”
Section: Hypothesissupporting
confidence: 87%
“…This is in the form of the view that this content features Youtubers who live a fun lifestyle, which is filled with several entertaining activities. More satisfied individuals tend to have a preference for certain personality attributes in someone they admire, which can be influenced by progress in that individual (Harrison et al, 2023). It can be concluded that the results of this study are in line with previous research conducted by Malik et al, (Malik et al, 2023) which states that Fun has a very good impact on improvement Overal Perceived Image owned by YouTubers.…”
Section: Hypothesissupporting
confidence: 87%